(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2020)
3D printing offers unique solutions for bone tissue regeneration with an opportunity to engineer scaffolds with the desired structure, shape, and porosity. Scaffold’s surface-to-cell interaction is critical for better tissue integration and regeneration. To achieve this, we have surface modified the 3D printed scaffolds with polydopamine (PDA) to evaluate the potential of the surface modification for bone regeneration.